Safety and efficacy of target-controlled infusion versus intermittent bolus administration of propofol for sedation in colonoscopy: a randomized controlled trial - Cuiabano, Igor Seror; de Miranda Garbin, Priscila; Módolo, Norma Sueli Pinheiro [UNESP]; do Nascimento, Paulo [UNESP] (Elsevier, 2022)
Background: Our objective was to compare the safety and efficacy of Target-Controlled Infusion (TCI) versus intermittent bolus of propofol for colonoscopy sedation. Methods: We conducted a randomized (1:1), single-blind, parallel-group superiority trial with fifty ASA I or II patients, both sexes, aged 18 to 65 years, Body Mass Index ≤ 30 kg.m−2, undergoing colonoscopy, allocated to receive propofol by TCI (effect-site, 2 μg.mL−1 plus 0.5 μg.mL−1 until unconsciousness and as necessary for agitation) or intermittent bolus (1 mg.kg−1 plus 0.5 mg.kg−1 every 5 minutes or as above). The primary safety outcome was the need for airway maneuvers and the primary efficacy outcome was the need for interventions to adjust the level of sedation. Secondary outcomes included incidence of agitation, propofol dose, and time to recovery. Results: The median (IQR) number of airway maneuvers and interventions needed to adjust sedation was 0 (0‒0) vs. 0 (0‒0) (p = 0.239) and 1 (0‒1) vs. 3 (1‒4) (p < 0.001) in the TCI and control groups, respectively. Agitation was more common in the intermittent bolus group ‒ 2 (0‒2) vs. 1 (0‒1), p < 0.001. The mean ± SD time to recovery was 4.9 ± 1.4 minutes in the TCI group vs. 2.3 ± 1.6 minutes in the control group (p < 0.001). The total propofol dose was higher in the TCI group (234 ± 46 µg.kg−1.min−1 vs. 195 ± 44 µg.kg−1.min−1 (p = 0.040)). Conclusions: During colonoscopy, TCI is as safe as intermittent bolus of propofol while reducing the incidence of agitation and the need for dose adjustments. However, intermittent bolus administration was associated with lower total propofol dose and earlier recovery.
Keywords: Colonoscopy; Deep sedation; Intravenous anesthetics; Propofol